ortho-Amide-Directed Oxidation of Internal Aryl Alkynes Mediated by Cerium(IV) Ammonium Nitrate - Su, Chieh-Fu; Hu, Wan-Ping; Vandavasi, Jaya Kishore; Liao, Chao-Cheng; Hung, Chen-Ya; Wang, Jeh-Jeng (Synlett, 2012)
A fascinating oxidation of alkynes mediated by CAN directed by the amide group to synthesize N-[2-(2-oxo-2-phenylacetyl)phenyl]benzamide derivatives under mild conditions is reported. Excellent yields were obtained with various substituents by this method.
Keywords: CAN; diketones; oxidation; internal aryl alkynes